BAHASA PEREMPUAN PADA MAJALAH FEMINA DAN SEKAR - Dewi, Azizah Kurnia (Humanis; Volume 4. No. 3. September 2013, 2013)
Women's language is closely related to gender. Spoken word (language) used by the women are more subtle than the language used by the men. The women tend to be more refined manners, (avoiding the use of bad words), the language standard, extensive use of tag questions, often use intonation rises, and many using feelings. In the current study examined women's language is written in the magazine Femina and Sekar.
Keywords: language , women, and gender